2021
DOI: 10.1002/adhm.202100436
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Mechanism of Aβ42 Fibril Growth on Surface of Graphene Oxides: Oxidative Degree Matters

Abstract: The filamentous β‐amyloid deposition has been regarded as the hallmark pathology of Alzheimer's disease (AD). Nanomaterials such as graphene oxides (GOs) have achieved significant progress in the therapy of AD, but the molecular pathway of the growth propagation remains challenging to investigate, especially on the surfaces of materials. The thermodynamics and kinetics of fibril elongation on GO surfaces with different oxidative degrees have been investigated by a combination of in vitro experiments and simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Sustainable nanotechnology requires a comprehensive understanding of the interactions between immune system and material including exposure pathways and fate in healthcare. [8,50] Our study of the interaction between immune cells and nanomaterials elucidated the immune effect. Our research provides fundamental guidance and experimental evidences for practical application of GO in the nanotechnology and unintended exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable nanotechnology requires a comprehensive understanding of the interactions between immune system and material including exposure pathways and fate in healthcare. [8,50] Our study of the interaction between immune cells and nanomaterials elucidated the immune effect. Our research provides fundamental guidance and experimental evidences for practical application of GO in the nanotechnology and unintended exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Circular dichroism (CD) spectroscopy is a simple and accurate method to determine the secondary structure of a protein in solution. As shown in Figure G, ERα exhibited typical peaks at 208 and 222 nm, representing the presence of α-helix . ERα was incubated with PSDalpha at 37 °C for 3 h and then irradiated for 15 and 30 min.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 3G, ERα exhibited typical peaks at 208 and 222 nm, representing the presence of α-helix. 37 ERα was incubated with PSDalpha at 37 °C for 3 h and then irradiated for 15 and 30 min. The typical peaks of αhelix decreased significantly after 15 min irradiation, indicating that the structure of ERα was ruined by the generated 1 O 2 .…”
Section: ■ Resultsmentioning
confidence: 99%
“…CD spectroscopy is a fast, simple, and accurate method to investigate the conformation of proteins. [ 27 ] As ER α mainly composed of α ‐helix, their CD spectra exhibited negative peaks in the far UV region (Figure 2D). Time dependent degradation of ER α at different solvent temperature indicated that pure ER α in PBS degraded at 50–55 °C (Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%